Highly Pathogenic New World and Old World Human Arenaviruses Induce Distinct Interferon Responses in Human Cells - Huang, Cheng (J Virol, 2015)
The arenavirus family includes several important pathogens that cause severe and sometimes fatal diseases in humans. The highly pathogenic Old World (OW) arenavirus Lassa fever virus (LASV) is the causative agent of Lassa fever (LF) disease in humans. LASV infections in severe cases are generally immunosuppressive without stimulating interferon (IFN) induction, a proinflammatory response, or T cell activation. However, the host innate immune responses to highly pathogenic New World (NW) arenaviruses are not well understood. We have previously shown that the highly pathogenic NW arenavirus, Junin virus (JUNV), induced an IFN response in human A549 cells. Here, we report that Machupo virus (MACV), another highly pathogenic NW arenavirus, also induces an IFN response. Importantly, both pathogenic NW arenaviruses, in contrast to the OW highly pathogenic arenavirus LASV, readily elicited an IFN response in human primary dendritic cells and A549 cells. Coinfection experiments revealed that LASV could potently inhibit MACV-activated IFN responses even at 6 h after MACV infection, while the replication levels of MACV and LASV were not affected by virus coinfection. Our results clearly demonstrated that although all viruses studied herein are highly pathogenic to humans, the host IFN responses toward infections with the NW arenaviruses JUNV and MACV are quite different from responses to infections with the OW arenavirus LASV, a discovery that needs to be further investigated in relevant animal models. This finding might help us better understand various interplays between the host immune system and highly pathogenic arenaviruses as well as distinct mechanisms underlying viral pathogenesis. IMPORTANCE Infections of humans with the highly pathogenic OW LASV are accompanied by potent suppression of interferon or proinflammatory cytokine production. In contrast, infections with the highly pathogenic NW arenavirus JUNV are associated with high levels of IFNs and cytokines in severe and fatal cases. Arenaviruses initially target macrophages and dendritic cells, which are potent IFN/cytokine-producers. In human macrophages, JUNV reportedly does not trigger IFN responses. We here demonstrated that JUNV activated IFN responses in human dendritic cells. MACV, another highly pathogenic NW arenavirus, also activated IFN responses. LASV did not induce detectable IFN responses, in spite of higher replication levels, and blocked the MACV-triggered IFN response in a coinfection assay. Although these viruses are highly pathogenic to humans, our study highlights distinct innate immune responses to infections with the NW arenaviruses JUNV and MACV and to infection with the OW arenavirus LASV and provides important insights into the virus-host interaction and pathogenesis.